Zmiany w narządzie wzroku u chorych z przewlekłym zapaleniem wątroby typu C leczonych interferonem - Mrugacz, Małgorzata; Lebensztejn, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
The pathology of the liver is associated with many disorders including the eye. We described ocular changes following hepatitis C. The most common ophthalmic findings in hepatitis C patients treated with interferon-α involve keratoconjunctivitis, scleritis, dry eye syndrome, uveitis, retinopathy, retinal hemorrhages, anterior ischemic optic neuropathy, retinal vascular changes and macular oedema, as well as electroretinogram, visual field and OCT abnormalities.